Fractally Generated Microstrip Bandpass Filter Designs Based on Dual-Mode Square Ring Resonator for Wireless Communication Systems - Jawad K. Ali (Al-Khwarizmi College of Engineering – University of Baghdad, 2019)
A novel fractal design scheme has been introduced in this paper to generate microstrip bandpass filter designs with miniaturized sizes for wireless applications. The presented fractal scheme is based on Minkowski-like prefractal geometry. The space-filling property and self-similarity of this fractal geometry has found to produce reduced size symmetrical structures corresponding to the successive iteration levels. The resulting filter designs are with sizes suitable for use in modern wireless communication systems. The performance of each of the generated bandpass filter structures up to the 2nd iteration has been analyzed using a method of moments (MoM) based software IE3D, which is widely adopted in microwave research and industry. Results show that these filters possess good transmission and return loss characteristics, besides the miniaturized sizes meeting the design specifications of most of wireless communication systems.